2016
DOI: 10.1016/j.str.2016.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into the Mechanism of Calmodulin Inhibition of the EAG1 Potassium Channel

Abstract: Summary The human EAG1 potassium channel belongs to the superfamily of KCNH voltage-gated potassium channels that have roles in cardiac repolarization and neuronal excitability. EAG1 is strongly inhibited by Ca2+-calmodulin (CaM) through a mechanism that is not understood. We determined the binding properties of CaM with each one of three previously identified binding sites (BDN, BDC1 and BDC2), analyzed binding to protein stretches that include more than one site, and determined the effect of neighboring glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Consistently, by visualizing the interaction between YFP-labeled CaM and Cerulean-labeled hEAG1 in mammalian cells by Förster resonance energy transfer (FRET), Gonçalves et al [ 43 ] found that the high affinity BD-N binding domain and the second C-terminal binding domain BD-C2 are predominantly involved in EAG1 channel inhibition by Ca 2+ . Consistently, a recent isothermal titration calorimetry (ITC) combined with crystal structure of the CaM-BDC2 complex study revealed a high affinity between CaM and BD-C2 [ 44 ]. Mutations at these two sites completely abolished CaM binding to hEAG1, indicating that the BD-N and BD-C2 binding domains are required for CaM binding.…”
Section: Endogenous Regulation Of Eag1 Channelsmentioning
confidence: 66%
“…Consistently, by visualizing the interaction between YFP-labeled CaM and Cerulean-labeled hEAG1 in mammalian cells by Förster resonance energy transfer (FRET), Gonçalves et al [ 43 ] found that the high affinity BD-N binding domain and the second C-terminal binding domain BD-C2 are predominantly involved in EAG1 channel inhibition by Ca 2+ . Consistently, a recent isothermal titration calorimetry (ITC) combined with crystal structure of the CaM-BDC2 complex study revealed a high affinity between CaM and BD-C2 [ 44 ]. Mutations at these two sites completely abolished CaM binding to hEAG1, indicating that the BD-N and BD-C2 binding domains are required for CaM binding.…”
Section: Endogenous Regulation Of Eag1 Channelsmentioning
confidence: 66%
“…It is important to note that both hERG and rEAG channel structures show the S4 voltage sensor in the up position, which agrees well with the electrical field of 0 mV in the experimental setup and the open gate of the hERG channel but not with the conformational state of the closed rEAG. Like other members of the EAG subfamily, rEAG is inhibited by calmodulin in complex with Ca 2þ (CaM/Ca 2þ ) (10)(11)(12)(13)(14), and the structure provides an extraordinary view of the two proteins together. CaM/Ca 2þ either stabilizes the closed gate, forces it closed, or somehow decouples it from the VSDs while they remain in their ''up'' or activated positions.…”
Section: An Open and A Closed Channelmentioning
confidence: 99%
“…In any event, the take-home message is that there is a~10 Å incertitude regarding the relative position of the CaMBD. Similar to SK channels, trafficking of KCNQ channels to the membrane requires CaM [57,96,[102][103][104][105], and current density is affected by CaM availability: increases, decreases, or no effects upon CaM overexpression have been reported [106][107][108][109][110]. Since the CaMBD has a notorious aggregation tendency when produced in bacteria in the absence of CaM, it is thought that CaM is a constitutive auxiliary subunit of KCNQ channels.…”
Section: The Pip 2 Site Delineated By Cam and Helices B/c Linker Is Fmentioning
confidence: 99%